2022
DOI: 10.1038/s41467-022-29423-0
|View full text |Cite|
|
Sign up to set email alerts
|

Functional control of a 0.5 MDa TET aminopeptidase by a flexible loop revealed by MAS NMR

Abstract: Large oligomeric enzymes control a myriad of cellular processes, from protein synthesis and degradation to metabolism. The 0.5 MDa large TET2 aminopeptidase, a prototypical protease important for cellular homeostasis, degrades peptides within a ca. 60 Å wide tetrahedral chamber with four lateral openings. The mechanisms of substrate trafficking and processing remain debated. Here, we integrate magic-angle spinning (MAS) NMR, mutagenesis, co-evolution analysis and molecular dynamics simulations and reveal that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 90 publications
0
19
0
Order By: Relevance
“…REDOR and NERRD measurements on specifically methyl-labeled samples showed that the loop samples a wide conformational space within the cavity and is able to stabilize ligands in the active site, whereby a conserved histidine plays a key role. The data provided strong evidence for the functional importance of highly dynamic parts of enzymes and the potential of MAS NMR to investigate their dynamics at atomic resolution …”
Section: Structural and Dynamical Biology By 1h-detected Mas Nmrmentioning
confidence: 83%
See 1 more Smart Citation
“…REDOR and NERRD measurements on specifically methyl-labeled samples showed that the loop samples a wide conformational space within the cavity and is able to stabilize ligands in the active site, whereby a conserved histidine plays a key role. The data provided strong evidence for the functional importance of highly dynamic parts of enzymes and the potential of MAS NMR to investigate their dynamics at atomic resolution …”
Section: Structural and Dynamical Biology By 1h-detected Mas Nmrmentioning
confidence: 83%
“…The data provided strong evidence for the functional importance of highly dynamic parts of enzymes and the potential of MAS NMR to investigate their dynamics at atomic resolution. 361 Using the same model system, Schanda and co-workers demonstrated that 1 H-detected fast MAS NMR combined with a tailored isotope labeling scheme can provide insight into central functional and structural role of aromatic residues. A particular difficulty in observing their resonances in large proteins is dynamics and limited spectral dispersion.…”
Section: H-based Dynamicsmentioning
confidence: 99%
“…However, the interconversion between these two states happens on a much faster timescale than any other protein activity (49). Schanda et al found that the enzymatic activity of the TET2 aminopeptidase is controlled by the conformational equilibrium of a highly dynamic loop in the catalytic chamber (50). Also, the turnover in the HisFH enzyme complex is dictated by the population of the active state, with the conversion between ground and active state taking place on a faster time scale than enzymatic activity (51).…”
Section: Discussionmentioning
confidence: 99%
“…However, modeling dynamics this way beyond a two-state exchange is challenging, due to experimental limitations and poor timescale separation. In effect, we are limited to highly simplified models of the complex underlying dynamics of our data where the structure of states often remain elusive or ambiguous [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%